(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The play begins with Mala, the protagonist is talking to the counselor, because she is suffering from a mental stress, her behavior is not normal. She wants to come out from her horrible past; Mahesh Dattani discloses the inner conflict of her mind. She wants to disclose the truth to her parents and wants to tell what happened to her but no one was there to listen her. Mala has her traumatic past experiences. She is sexually abused by her maternal uncle Vinay. Vinay is a man who has beastly passion and always tries to search such victims those can be easily preyed and can not disclose the truth to anybody. If such victim disclose in front of someone no one believe on her /him. In the play Dattani unveils the burning issues of society such as child sexual abuse, molestation and patriarchy, etc.